Pemberian Air Rebusan Kacang Hijau (Phaseolus radiatus) dan Daun Adas (Foeniculum vulgare) Pada Ibu Menyusui Terhadap Berat Badan Bayi Usia 0-6 Bulan - Anik Sri Purwanti (Oksitosin : Jurnal Ilmiah Kebidanan, 2023)
Mother's Milk (ASI) is the main source of nutrition for babies. Unfortunately many mothers choose formula milk instead. The diet of breastfeeding mothers indirectly affects the composition and production of breast milk. Malnutrition not only interferes with the physical condition of the mother but also reduces the quantity and quality of breast milk. Drinking water infused with fennel seeds and mung beans is said to be effective in counteracting this. We wanted to study whether feeding mothers green bean (Phaseolus radiatus) and fennel (Foeniculum vulgare) water had an impact on the birth weight of their babies between the ages of 0 and 6 months. Researchers used a pre-experimental approach and sampling method aiming to recruit 17 breastfeeding mothers with infants between the ages of 0 and 6 months. Statistics show a significant difference (p 0.000) using the Paired T-Test in SPSS. Mung bean water (Phaseolus radiatus) and fennel leaves (Foeniculum vulgare) given to breastfeeding mothers had an effect on the weight of newborns between the ages of 0 and 6 months, and this effect was statistically significant (p 0.000). Breastfeeding women are advised to drink a mixture of mung bean water and fennel leaves to help regulate milk production and ensure that the baby's weight gain stays within a healthy range.